2017
DOI: 10.1016/j.dnarep.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair and systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with no known cure that affects at least five million people worldwide. Monozygotic twin concordance and familial aggregation studies strongly suggest that lupus results from genetic predisposition along with environmental exposures including UV light. The majority of the common risk alleles associated with genetic predisposition to SLE map to genes associated with the immune system. However, evidence is emerging that implicates a role for aber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 111 publications
2
18
0
Order By: Relevance
“…During the past decade, significant progress has been made to elucidate a role for aberrant DNA repair in the development of lupus. Recent evidence indicates that patients with SLE have higher levels of DNA damage than normal subjects, and that polymorphisms in genes involved in the preservation of the genomic stability increase the risk for SLE (32)(33)(34). Furthermore, experience from animal models reinforces the importance of defective repair in the development of SLElike disease (35), suggesting that therapeutic potential of targeting DNA damage and DNA repair responses in SLE pathogenesis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, significant progress has been made to elucidate a role for aberrant DNA repair in the development of lupus. Recent evidence indicates that patients with SLE have higher levels of DNA damage than normal subjects, and that polymorphisms in genes involved in the preservation of the genomic stability increase the risk for SLE (32)(33)(34). Furthermore, experience from animal models reinforces the importance of defective repair in the development of SLElike disease (35), suggesting that therapeutic potential of targeting DNA damage and DNA repair responses in SLE pathogenesis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Called as "the Great Imposter," systemic lupus erythematosus (SLE) is a chronic and complex autoimmune disease with multisystem manifestations [1,2]. The disease prevalence is estimated about 5 million people worldwide, and it occurs mostly before the age of 45 years [3][4][5]. The loss of central and peripheral tolerance to self, as a result of genetic susceptibility or environmental factors, is proposed to be a crucial first step in the SLE development [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Called as "the Great Imposter", systemic lupus erythematosus (SLE) is a chronic and complex autoimmune disease with multi-system manifestations in which many questions about its etiology remain unanswered [1,2]. The disease prevalence rate estimated about 5 million people worldwide and it occurs mostly before age 45 years [3][4][5]. The loss of central and peripheral tolerance to self is proposed to be a crucial first step in the progress of SLE [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, to construct trained BNs and identify significant nodes and edges in SLE, as a complex autoimmune disease, we (1) integrated peripheral blood mononuclear cells (PBMCs) microarray gene expression by cross-platform normalization [23]; (2) employed SLE, TCR and BCR signaling pathways as underlying structures of BNs;(3) estimated the parameters of BNs by integrated datasets [22,24]; (4) merged the obtained significant parameters of BNs in desired pathways as "meta-analysis" data integration [23]; (5) highlighted signaling pathways alterations involved in the SLE pathogenesis. Finally, we (6) demonstrated that some of the genes and intergenic relationships have a vital role and can be used as effective targets for therapeutic intervention in SLE patients.…”
Section: Introductionmentioning
confidence: 99%